The Informational Advantage of Foreign Investors: An Empirical Study of the Swedish Bond Market - Patrik Säfvenblad (Sveriges Riksbank, 1999)
This paper uses a unique dataset on daily capital ows to the Swedish bond market to analyse the relative information endowment of domestic and foreign investors. Using the standard framework of a noisy rational expectations equilibrium, it is concluded that foreign investors are on average better informed than domestic investors about the future value of sek denominated bonds. The better information of foreign investors is shown to be related to both pure Swedish factors as well as international factors.
Keywords: E43; G12; G14; G15; 330; Bond prices; capital flows; foreign investors; informed investors; intrest rate determination